2013
DOI: 10.1186/1472-6920-13-87
|View full text |Cite
|
Sign up to set email alerts
|

Motivational profiles of medical students: Association with study effort, academic performance and exhaustion

Abstract: BackgroundStudents enter the medical study with internally generated motives like genuine interest (intrinsic motivation) and/or externally generated motives like parental pressure or desire for status or prestige (controlled motivation). According to Self-determination theory (SDT), students could differ in their study effort, academic performance and adjustment to the study depending on the endorsement of intrinsic motivation versus controlled motivation. The objectives of this study were to generate motivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
169
6
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(230 citation statements)
references
References 33 publications
19
169
6
10
Order By: Relevance
“…However, there was no significant difference between the genders in the controlled motivation group. This is in contrast to the study done by Kusurkar et al 10 where intrinsic motivation was found to be statistically not significant, while males had significantly more controlled motivation than the females. Study done among the Swiss medical students found that women plan their career more purposefully than men.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, there was no significant difference between the genders in the controlled motivation group. This is in contrast to the study done by Kusurkar et al 10 where intrinsic motivation was found to be statistically not significant, while males had significantly more controlled motivation than the females. Study done among the Swiss medical students found that women plan their career more purposefully than men.…”
Section: Discussioncontrasting
confidence: 99%
“…However it was quite different compared to low motivation (LILC) and status motivation (LIHC). This finding was similar with the study done by Vansteenkiste et al 20 along with Kusurkar et al 10 thus supporting the study findings from this study.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…9 By way of example of evaluating teaching and assessment changes, Bevan et al 10 demonstrated that traditional lectures/examinations encouraged surface learning, whilst student-centered workshops/multiple examinations throughout a biochemistry subject encouraged deep learning. With regard to the health professions, there are numerous examples 3,[11][12][13][14][15][16] where the SPQ and it's more recent incarnation, the revised 2 factor version of the SPQ (R-SPQ-2F), 9 have been used. Interested readers are encouraged to explore the summary of learning approaches in Data were entered into Microsoft Excel.…”
Section: Introductionmentioning
confidence: 99%
“…5 Self-determination theory (SDT) provides a useful framework with which to consider students' motivation. According to this framework, the motivation to learn is driven by 3 psychological needs: a sense of relatedness, a sense of autonomy, and a sense of competence.…”
Section: Encourage Self-motivationmentioning
confidence: 99%